2014
DOI: 10.3389/fninf.2014.00007
|View full text |Cite
|
Sign up to set email alerts
|

Multi-atlas segmentation of subcortical brain structures via the AutoSeg software pipeline

Abstract: Automated segmenting and labeling of individual brain anatomical regions, in MRI are challenging, due to the issue of individual structural variability. Although atlas-based segmentation has shown its potential for both tissue and structure segmentation, due to the inherent natural variability as well as disease-related changes in MR appearance, a single atlas image is often inappropriate to represent the full population of datasets processed in a given neuroimaging study. As an alternative for the case of sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 101 publications
(93 citation statements)
references
References 49 publications
0
93
0
Order By: Relevance
“…Yet, a growing number of methods recognize the value in the deformation fields themselves and propose to use information about the amount of deformation in the computations of the fusion weights. For example, Commowick and Malandain (2007) used the Euclidean norm of the deformation, Ramus et al (2010) used its Jacobian determinant, and Wang et al (2014b) used its harmonic energy.…”
Section: Survey Of Methodological Developmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, a growing number of methods recognize the value in the deformation fields themselves and propose to use information about the amount of deformation in the computations of the fusion weights. For example, Commowick and Malandain (2007) used the Euclidean norm of the deformation, Ramus et al (2010) used its Jacobian determinant, and Wang et al (2014b) used its harmonic energy.…”
Section: Survey Of Methodological Developmentsmentioning
confidence: 99%
“…These approaches introduce additional complexity to the system, but can outperform standard similarity measures in the atlas selection task. Another approach to increase the efficiency and accuracy of atlas selection utilizes clustering, where the atlases, possibly together with the novel image(s), are analyzed to identify clusters of similar cases using methods such as k-means (Nouranian et al, 2014), affinity propagation (Langerak et al, 2013) and Floyd’s algorithm (Wang et al, 2014b). Then, cluster representatives (or exemplars) are used for the initial search of the most relevant atlases.…”
Section: Survey Of Methodological Developmentsmentioning
confidence: 99%
“…Datasets were processed using AutoSeg_3.3.2 segmentation package (87) to get the volumes of brain white mater (WM), gray matter (GM), cerebrospinal fluid (CSF), cortical (temporal visual area, temporal auditory area, prefrontal, frontal, parietal and occipital lobes) and subcortical (hippocampus, amygdala) brain areas. Image processing steps included: 1) averaging T1 and T2 images to improve signal-to-noise ratio, 2) intensity inhomogeneity correction, 3) rigid body registration of the subject MRI to the three or the six months UNC-Emory infant RM atlases (35), 4) tissue segmentation and skull-stripping, 5) registration of the atlas to the subject’s brain to generate cortical parcellations (affine followed by deformable SyN/ANTS registration), 6) manual editing of the amygdala and hippocampus was done on all scans using previously published neuroanatomical boundaries (31).…”
Section: Methodsmentioning
confidence: 99%
“…The concept of a multi-atlas approach has recently gained traction for label mapping (Wu et al 2015; Wang et al 2014). Specifically, more accurate individual subject labeling can be achieved by mapping to multiple templates.…”
Section: Discussionmentioning
confidence: 99%
“…Existing NHP-specific tools also can demonstrate high failure rates, even for experienced users. Our own experience with several NHP-specific tools (Wang et al 2014; Fedorov et al 2011) has demonstrated failure rates as high as 50%.…”
Section: Introductionmentioning
confidence: 99%